Impact of home-based family planning counselling and referral on modern contraceptive use in Karachi, Pakistan: a retrospective, cross-sectional matched control study. Issue 9 (23rd September 2020) - Hackett, Kristy; Henry, Elizabeth; Hussain, Imtiaz; Khan, Mirbaz; Feroz, Khalid; Kaur, Navdep; Sato, Ryoko; Soofi, Sajid; Canning, David; Shah, Iqbal
Abstract : Objectives: To assess: (1) the impact of a reproductive health program on modern contraceptive use from baseline to program close; (2) the sustained impact from baseline to follow-up 36 months later; and (3) the exposure-adjusted impact at program close and follow-up. Design: Retrospective, cross-sectional matched control study. Setting: Karachi, Pakistan. Participants: 2561 married women aged 16–49 years. Interventions: The Willows Program, a community-based family planning counselling and referral program implemented from 2013 to 2015. Primary and secondary outcome measures: The primary outcome was community-level modern contraceptive prevalence rate (mCPR), measured for January 2013 (baseline), June 2015 (program close) and at follow-up 36 months later. A secondary outcome was exposure-adjusted mCPR (among women reporting a family planning home visit) at program close and at follow-up. Results: There was no significant effect on community-level mCPR at program close (2.4 percentage point increase in intervention over comparison; 95% CI −2.2 to 7.0) or at follow-up (1.9 percentage point decrease; 95% CI −6.7 to 2.8). Only 18% of women in the intervention area reported receiving a family planning visit in the preceding 5 years. Among those reporting a visit, we observed a significant 10.3 percentage point increase (95% CI 4.6 to 15.9) from baseline to close, and a non-significant 2.0 percentage point increase (95% CI −3.8 to 7.8) from baseline to follow-up, relative to matched women in the comparison area. The cost per new modern method user was US1089, while the cost per user-year during the intervention period was US455. Conclusions: The program had a positive short-term effect on women who received a family planning visit; however, this effect was not sustained. Program coverage was low and did not significantly increase community-level family planning use. Findings highlight the need to increase community coverage of high-quality counselling and contextually relevant interventions for family planning demand generation.